Pengembangan Media Pembelajaran Interaktif Berbasis Android Untuk Pembelajaran Ilmu Pengetahuan Alam Kelas VIII SMP - Jodi Hardika; M. Yakub Iskandar; Nofri Hendri; Ulfia Rahmi (STKIP Pesisir Selatan, 2024)
Learning natural sciences in class requires the right media so that it is more impressive about the nature that is brought to class. Media that can integrate natural conditions can be brought into the classroom to make the learning process more real. One way is to use interactive multimedia, this media is used in the learning process so that students are able to learn the material in real life without having to go directly into nature. This research uses R&D (Research and Development) research with a 4-D model with a flow of definition, planning, development and deployment. The validity results were 4.88 or 97.7% from the first media expert in the